Durabilitas Mortar Geopolimer Campuran Abu Terbang (FA) Dan Abu Sawit(POFA) Di Lingkungan Gambut - Yudhi Salman Dwi Satya; Monita Olivia; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
This research study presents the durability of OPC and geopolymer mortars prepared from the combination of palm oil fuel ash (POFA) and fuel ash (FA) as cement replacement and elements of Si and Al was activated by alkaline solution. Alkaline solution was prepared by combining sodium silicate and sodium hydroxide 14 M. The optimum mix proportions of geopolymer mortars with FA:POFA mass ratio of 90:10 was used together with alkaline solution. The ratio of sodium silicate solution to sodium hydroxide solution by mass was 2.5:1. The mass ratio of sand to blended ashes was 2,75:1. Test specimens 5×5×5 cm cube were prepared and cured at room temperature (28ºC) for 3 days and heat-cured at 110ºC for 24 hours, later cured back at room temperature for 7 days. respectively. Then specimens were immersed in distilled water and peat water. This research resulted in changes of compressive strength the OPC and geopolymer mortars, after immersed in distilled water for 28 days mortar OPC was increasing the compressive strength while geopolymer mortar was decreasing of compressive strength. Furthermore, in the immersed peat water, OPC and geopolymer mortars tend to decreased the compressive strength. The percentage porosity value of both types of mortar were immersed in peat water has increased compared to the immersed in distilled water. The test results revealed that durability of geopolymer mortar in peatlands not as good as OPC mortar due to many factors that lead to a decrease the quality of geopolymer mortar.Keywords : Durability, mortar geopolymer, fuel ash, palm oil fuel ash, peat water